The use of a non-medicated dressing for superficial-partial thickness burns in children: a case series and review. (December 2019) - Kusu-Orkar, Ter-Er; Islam, Umar; Hall, Benjamin; Araia, Evan; Allorto, Nikki
Background: Cutimed ® Sorbact ® is a dressing marketed as having antimicrobial properties and easy application without the threat of antibiotic resistance and difficult accessibility. There is little evidence on the clinical outcomes of the use of Cutimed ® Sorbact ® in adults and currently no evidence of use of Cutimed ® Sorbact ® on superficial-partial thickness burn injuries in children. Objective: To summarise the clinical outcome of burn wounds in children with superficial-partial thickness burns in which Cutimed ® Sorbact ® was used. Method: An observational case series was conducted in Edendale Hospital, Pietermaritzburg, South Africa over the course of four weeks. Patients where included if they were aged < 10 years and had a ⩽ 15% superficial-partial burn. The primary outcome measure was time to 95% re-epithelialisation. Secondary outcome measures included wound complications, adverse healing and number of dressing changes. Results: Ten patients (five girls, five boys; age range = 11 months–8 years) were included in this case series. All participants had a type VI Fitzpatrick skin type and 80% of burns were hot water burns. Of all patients treated with Cutimed ® Sorbact ®, 50% healed within seven days, 70% within 14 days and 100% within 21 days. There was only one wound complication noted in this study and there was no adverse healing in any burn wounds. The mean number of dressing changes was 1.4 (range = 1–2) and length of hospital stay was in the range of 0–11 days (mean = 5.1 days). Conclusion: Cutimed ® Sorbact ® is a safe, useful and cost-effective dressing that should be used as an alternative for superficial-partial burns in children. Lay Summary: Cutimed ® Sorbact ® is a dressing used for burns that has unconventional ways to fight bacteria. This allows the dressing to work without becoming resistant to antibiotics and it is also easy to apply. In order to find out how well this dressing works in children, a study was performed in a South African hospital, Edendale, over four weeks. The main aim of the study was to find out how long the wounds took to heal when Cutimed ® Sorbact ® was put on a burn in children aged < 10 years. The study found that 50% of children's burns healed within seven days and 100% healed within 21 days. There was one complication that was resolved and children stayed in hospital for an average of five days. Therefore, Cutimed ® Sorbact ® is a safe and cost-effective dressing that should be considered as an alternative for burns in children.